An Unprecedented Interpenetrating Structure Built from Two Differently Bonded Frameworks: Synthesis, Characteristics, and Efficient Removal of Anionic Dyes from Aqueous Solutions. Issue 33 (2nd May 2019) - Wang, Chih‐Ling; Hsieh, Jui; Lee, Li‐Wei; Wu, Jing‐Yun; Hsiao, Pu‐Yen; Chu, Jean‐Ho; Wang, Chih‐Min
Abstract: The first example of one single crystal (NTOU‐5) containing two different organic‐inorganic hybrid open‐framework structures was obtained using a hydro(solvo)thermal method and structurally characterized by single‐crystal X‐ray diffraction. Remarkably, under the same synthetic conditions, the zinc ions are respectively coordinated by oxalic acid (OX) and 1, 2, 4, 5‐tetrakis(imidazol‐1‐ylmethyl)benzene (TIMB) linkers to form two significantly different frameworks: anionic [Zn2 (OX)3 ] 2− and cationic [Zn(TIMB)] 2+ networks that interweave with each other to give an unprecedented interpenetrating structure with two differently‐bonded open‐frameworks. From the inorganic chemistry perspective, it is extremely difficult to control to which metal center the oxygen‐donor linkers or/and nitrogen‐donor ligands bind. A mixed Co/Zn analogue was also obtained by a similar method. The single‐crystal XRD and EDS analyses indicate that the octahedral Zn ions of the anionic framework are replaced by cobalt cations, whereas the Zn ions in the tetrahedral positions of the cationic networks remain intact. This leads to the formation of the interpenetrating analogue with a mixed metal composition. Furthermore, NTOU‐5 shows structural stability and efficiently removes organic dyes from aqueous solutions at concentrations of 10 ppm. Abstract : Mix it up : For the first time, zinc ions are coordinated either by oxygen‐donor ligands or by nitrogen‐donor linkers in the same synthetic conditions to form significantly distinct anionic and cationic networks that interweave with each other to give an unprecedented class of interpenetrating structure with two differently‐ bonded open‐frameworks, NTOU‐5. A mixed metal analogue was also obtained by a similar synthesis method. Moreover, NTOU‐5 efficiently achieves water remediation by removing organic dyes from aqueous solutions, even at low concentration (10 ppm).